Determinants and Repercussions of the Composition of Capital Inflows - Carlson, Mark.; Hernandez, Leonardo (Washington, D.C. : International Monetary Fund, 2002)
The Mexican, Asian, and Russian crises of the mid- and late 1990s have renewed interest among policymakers in the determinants and effects of private capital inflows. This paper analyzes whether policies can affect the composition of capital inflows and whether different compositions aggravate crises. The results support the view that, while fundamentals matter, capital controls can affect the mix of capital inflows that countries receive. The results also show that during the Asian crisis, countries with more yen-denominated debt faired worse, while during the Mexican crisis larger short-term debt stocks increased the severity of the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet